Bridge Inspection with an Off-the-Shelf 360° Camera Drone - Andreas Humpe (Drones, 2020)
The author proposes a new approach for bridge crack detection by a 360° camera on top of a drone. Traditionally, bridge inspection is performed manually and although the use of drones has been implemented before, researchers used standard high definition cameras underneath the drone. To make the approach comparable to the conventional approach, two bridges were selected in Germany and inspected for cracks and defects by applying both methods. The author follows an engineering design process and after developing a prototype of the drone with a 360° camera above the body of the drone, the system is built, tested, and the bridges are inspected. First, the critical parts of the bridges are inspected with an off-the-shelf drone with a high definition camera underneath the drone. The results provide a benchmark for comparison. Next, the new approach to bridge inspection by using a 360° camera on top of the drone is tested. The images of the critical parts of the bridge that were taken with the 360° camera on top of the drone are analyzed and compared to the images of the conventional approach with the camera underneath the drone. The results show that a 360° camera can be used for crack and defect detection with similar results to a standard high definition camera. Furthermore, the 360° camera is more suitable for inspecting corners or the ceiling of, e.g., an arch bridge.